As subversões do desejo feminino: um olhar sobre a subjetivação das mulheres a partir do caso Dora - SOUZA , Jakeline Conceição Guimarães de (2024)
ABSTRACT: This study presents the concepts and impasses that cross the construction of female subjectivity, considering the psychological, social and historical aspects involved in this construction. Thus, the central aim of the study sought understand according to the principles of psychoanalysis how female subjectivity contemporary art is constructed in conjunction with the work “Fragments of the Analysis of a Case of Hysteria” published by Sigmund Freud in 1905. Woman and hysteria allows the construction of knowledge that is shaped from culture and discourses organizational structures that permeate relationships and mark subjectivity. In this way, the study presents different conceptions about subjectivity, considering the culture, historical and social aspects and the patriarchal periodas landmarks for the constitution of female subjectivity in contemporary times. Consisting of a theoretical research through which it is proposed to revisit the classic works of Freud and Lacan, as well as how contemporary authors constructed knowledge entangled in the feminine field, cartography was used as a method, raising the following question: How can Psychoanalysis understands the construction of female subjectivity in contemporary times based on the concepts of desire, body and symptom. The woman builds her subjectivity from a desire that initially appears subjected to the Other, in a attempt to detach yourself from this Other uses your desire to discover your identity and their roles in society. Therefore, desire as a componente constituent of subjectivity allows discoveries in the body. The second componente constitutive of female subjectivity is the body, which presents itself in several facets, linked to the social, psychological and psychoanalytic field, the body is the access route to truth of the subject that presents itself through symptoms. The third constitutive field of subjectivity is the symptom is crossed by psychoanalytic discourse as reveals not the truth of the disease, but the truth of the subject of the unconscious. The Dora case is a milestone in the construction of psychoanalysis as itportrays hysteria, bringing together fundamental concepts such as desire, body and symptom. Dora, hysterical patient experiences on his body the marks of the dominant discourse of a patriarchal era. Therefore the symptomatology presented by Dora differs from the symptoms presented by hysterical women in contemporary times, as in contemporary times Symptoms present themselves under a new form of subjective organization. While Dora transfers to the body the psychic marks repressed by a dominant culture, contemporary hysterical women defy the master’s discourse allowed new forms of subjective organizations.